2016
DOI: 10.1111/1346-8138.13714
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of Korean patients with rhinophyma

Abstract: Rhinophyma results from hyperplasia of the sebaceous glands and connective tissue. Clinical features in Asian rhinophyma patients are largely underreported. In this study, we aimed to evaluate the clinical features of rhinophyma in Korean patients. We reviewed clinical photos and medical records of 39 Korean patients diagnosed with rhinophyma and assessed the severity and clinical course by using the classical National Rosacea Society index. The male : female ratio was 6.8:1, and over 90% of the patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…There might have been a broader variation of skin phototypes among the Caucasians in our study. Our study found that older males were more likely to have phymatous rosacea, consistent with findings of other studies …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There might have been a broader variation of skin phototypes among the Caucasians in our study. Our study found that older males were more likely to have phymatous rosacea, consistent with findings of other studies …”
Section: Discussionsupporting
confidence: 93%
“…Our study found that older males were more likely to have phymatous rosacea, consistent with findings of other studies. 15,16 The main triggers identified were sunlight, exposure, or heat.…”
Section: Discussionmentioning
confidence: 99%